The Effect of 4MAT Instructional Model on Teaching of Geometric Subjects - Temel Kösa, Elif Özlem Ardıç (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
The main purpose of this study was to examine the effect of the learning environment designed for teaching geometric subjects according to the 4MAT model on permanent learning. The study used a quasi-experimental design with control group and was carried out with 86 students (41 students in experimental and 45 students in control group) at a lower secondary school located in Trabzon. The data were collected with The Pre-test (ÖBT), The Achievement Test (BT) and The Retention Test (KT) which were developed by researchers and The Learning Style Inventory (ÖSE) which was developed by Kolb. The results of the study showed that the courses conducted according to the 4MAT teaching model were more effective on students' achievement and more permanent learning. It also showed that the common effect of teaching method and learning style on students' academic achievement was not significant. In this context, it was suggested that teachers who use different methods, techniques and strategies in their lessons should primarily determine their students’ learning styles.